THE EFFECT OF USING DRAMA TECHNIQUE IN TEACHING SPEAKING SKILL TO THE SECOND SEMESTER STUDENTS OF ISLAMIC ECONOMICS AT UNISNU JEPARA IN 2013/2014 - Dwi Erlin Effendi (Universitas Islam Nahdlatul Ulama Jepara, 2015)
Speaking is the basic tool of education and the most important skill in everyday life. However, the fact shows that generally many students are inhibited to speak English. Drama can foster language skills such as reading, writing, speaking and listening by creating a suitable context. Drama is a powerful language teaching tool that involves all of the students interactively all of the class period. Drama can also provide the means for connecting students??emotions and cognition as it enables students to take risks with language and experience the connection between thought and action. The objective of the study isinvestigating the effect of using drama technique in teaching speaking skill.The study employed a quantitative method, with quasi experimental design with non- equivalent control group. The subjects are the second semester students of Islamic Economics at UNISNU Jeparain academic year 2013/ 2014. The data will be obtained from the result pretest/ posttest. The result in speaking without drama is 65% and the average score is 75,94. Then, the calculation of T-test show that T count is higher than T Table. So, the speaking method by using drama is more effective than without using drama for helping student to improve their ideas of the second semester of Islamic Economy Students of UNISNU Jepara in the academic year of2013/2014.Keywords: speaking ability, dramaBerbicara adalah alat dasar pendidikan dan keterampilan yang paling penting dalam kehidupan sehari-hari. Namun, fakta menunjukkan bahwa pada umumnya siswa terhambat untuk berbicara bahasa Inggris. Drama dapat memupuk keterampilan bahasa seperti membaca, menulis, berbicara dan mendengarkan dengan menciptakan konteks yang sesuai. Drama adalah alat pengajaran bahasa yang kuat yang melibatkan semua siswa secara interaktif semua periode kelas. Drama juga dapat menyediakan sarana untuk menghubungkan students'emotions dan kognisi karena memungkinkan siswa untuk mengambil risiko dengan bahasa dan pengalaman hubungan antara pikiran dan tindakan. Tujuan dari studi untuk mengetahui efek menggunakan teknik drama dalam mengajar berbicara studi skill.metode yang digunakan adalah metode kuantitatif, dengan desain quasi eksperimen dengan kelompok kontrol non-setara. Subyeknya adalah mahasiswa semester II Ekonomi Islam di tahun akademik UNISNU Jeparain 2013 / 2014. Data tersebut diperoleh dari hasil pretest / posttest. Hasil dalam berbicara tanpa drama adalah65% dan skor rata-rata adalah 75,94. Kemudian, perhitungan acara T-test yang T hitung lebih tinggi dari T Tabel. Jadi, metode berbicara dengan menggunakan drama lebih efektif daripada tanpa menggunakan drama untuk membantu siswa untuk meningkatkan ide-ide mereka dari semester II Ekonomi Islam Mahasiswa UNISNU Jepara pada tahun akademik2013/2014. Kata Kunci : kemampuan berbicara, drama